2014
DOI: 10.1016/j.dam.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Tilted Sperner families

Abstract: Let A be a family of subsets of an n-set such that A does not contain distinct sets A and B with |A\B| = 2|B\A|. How large can A be? Our aim in this note is to determine the maximum size of such an A. This answers a question of Kalai. We also give some related results and conjectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 3 publications
2
21
0
Order By: Relevance
“…Given A,B[n] the subcube of P(n) spanned by A and B consists of all subsets of AB that contain AB. Kalai (see ) observed that scriptA is an antichain precisely if it does not contain A and B such that, in the subcube of P(n) spanned by A and B, A is the top point and B is the bottom point. He asked what happens if one ‘tilts’ this condition.…”
Section: Tilted Sperner Familiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Given A,B[n] the subcube of P(n) spanned by A and B consists of all subsets of AB that contain AB. Kalai (see ) observed that scriptA is an antichain precisely if it does not contain A and B such that, in the subcube of P(n) spanned by A and B, A is the top point and B is the bottom point. He asked what happens if one ‘tilts’ this condition.…”
Section: Tilted Sperner Familiesmentioning
confidence: 99%
“…Let p,q be coprime with p < q . Leader and Long proved that the largest ( p, q )‐tilted Sperner family in P(n) has size (qp+o(1))true(nn/2true), where the lower bound is obtained by considering the union of the q – p middle layers of the Boolean lattice (see for an explanation of this).…”
Section: Tilted Sperner Familiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kalai raised the question of how large a tilted Sperner family A ⊂ P[n] can be. In [13], Leader and the second author proved that such families satisfy |A| ≤ (1 + o(1)) n n/2 , which is asymptotically optimal. For sufficiently large n, the extremal families were also determined.…”
Section: Introductionmentioning
confidence: 99%